Comparison of Treatment Response of Different Drugs in Common Migraine (Medical Forum Monthly, 2024)
Objective: The study was carried out to assess and contrast the efficacy of different pharmacological interventions in individuals who have received the diagnosis of common migraine.Study Design: A longitudinal observational cohort research studyPlace and Duration of Study: This study was conducted at the Department of Neurology, Pak Emirates Military Hospital in Rawalpindi from Jan 2022 to Jan 2023.Methods: The cohort comprised 234 individuals diagnosed with common migraine according to the criteria of International Classification of Headache Disorders (ICHD-3). The medication regimens of the patients, which included Tricyclic antidepressants, Topiramate, beta-blockers, calcium channel blockers and antiepileptics, were utilized to classify them. The evaluation of treatment response was conducted at one, three, and six months after treatment using Migraine Treatment Response Score (MTRS).Results: The study revealed that females comprised the majority at 65.8%. The average age of the participants was 40±12 years. Over the course of six months, Tricyclic antidepressants demonstrated the most substantial enhancement in MTRS, as evidenced by scores increasing from 4.5±1.2 to 5.8±1.0 (p<0.05). Significant declines in frequency and intensity of attacks were noted in response to Tricyclic antidepressants: the former decreased by 4±2 to 2±1, while latter decreased by 7±2 to 4±2 (p<0.05). Although improvements in attack frequency and severity were observed across all drug classes, Tricyclic antidepressants exhibited the most significant efficacy. 50% of antiepileptic-treated patients reported being affected post-treatment, with Tricyclic antidepressants influencing 28%.Conclusion: After six-month evaluation of medications examined, Tricyclic antidepressants demonstrated the highest level of efficacy in management of common migraines. However, symptom relief was observed in all drug categories to varying degrees, emphasizing the importance of tailoring treatment plans to patient-specific characteristics.